Criação de materiais didáticos autorais para o ensino de língua portuguesa - Rigonatto, Mariana (2020)
This work, which has a cognitive-functional perspective, proposes an analysis of the process of creating teaching materials carried out by teachers in initial training. This proposal is based on the need to expand the offer of subjects in undergraduate courses that provide a reflection on the creation of teaching material and, therefore, some practice that helps teachers in initial training to leave the position of reproducers and performers of activities of which they do not participate in the elaboration and assume a creative / creative and authorial posture. We used, as a theoretical basis for the discussion about academic formation, some studies, especially those produced by Pimenta (1999), Kleiman (2001a), Antunes (2003, 2007,2009), Gatti (2010), Garcia-Reis ( 2017). For the question of authorship, we used the concepts proposed by the Philosophy of Language in Foucault (1999, 2002) and in Bakhtin (2003), which expand the perspectives for the various functions that order, control and constitute the subject-teacher-author. Finally, for the issue of teaching Portuguese language through authorial materials, the analysis was built based on the practice of productive teaching based on functionalism as a possibility of integration between text and grammar found in Antunes (2005, 2007), Travaglia (2009), Neves (2010), Casseb-Galvão (2011), Silva (2017). Methodologically, it was proposed that, at first, four interns from the last period of the UFG Literature course should carry out a systematic study on the elaboration of didactic material. In a second step, the trainees elaborated questions to be applied in an elementary school class. In a third moment, they applied the questions, evaluated the validity of the proposal and reworked the questions. At the beginning and at the end of the process, there were interviews with the interns. As a result of the research, it was realized that future teachers feel the need to have greater contact with the practice of preparing teaching materials. There are important perceptions about the texts in the materials prepared alongside some difficulties that need to be addressed, such as the elaboration of the more specific statements of the author's activities. Works of this nature contribute to reflect on practices in the teaching of Portuguese and the needs that emerge from day to day.